2023
DOI: 10.3389/fimmu.2023.1055457
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles and protective mechanisms of neutralizing antibodies against SARS-CoV-2 infection and their potential clinical implications

Abstract: Neutralizing antibodies (NAbs) are central players in the humoral immunity that defends the body from SARS-CoV-2 infection by blocking viral entry into host cells and neutralizing their biological effects. Even though NAbs primarily work by neutralizing viral antigens, on some occasions, they may also combat the SARS-CoV-2 virus escaping neutralization by employing several effector mechanisms in collaboration with immune cells like natural killer (NK) cells and phagocytes. Besides their prophylactic and therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 206 publications
0
18
0
Order By: Relevance
“…No significant difference between visits for the CNI was found in the conducted study as reported before 6 . The genetic distance between the infection and Delta variant could account for the absence of an increase in cross‐neutralization as observed for Alpha/Beta variants 12,13 . Most likely the affinity maturation of certain wild‐type specific neutralizing epitopes B cells may account for this increase 13 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…No significant difference between visits for the CNI was found in the conducted study as reported before 6 . The genetic distance between the infection and Delta variant could account for the absence of an increase in cross‐neutralization as observed for Alpha/Beta variants 12,13 . Most likely the affinity maturation of certain wild‐type specific neutralizing epitopes B cells may account for this increase 13 .…”
Section: Discussionmentioning
confidence: 60%
“…6 The genetic distance between the infection and Delta variant could account for the absence of an increase in cross-neutralization as observed for Alpha/Beta variants. 12,13 Most likely the affinity maturation of certain wild-type specific neutralizing epitopes B cells may account for this increase. 13 The report highlights for the first time that the dynamics of S1/S2 IgG may anticipate the dynamics of cross-neutralization capacity against Delta at 3 months PSO, but not at late time points.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Alternatively, post-binding inhibition effector mechanisms achieve the elimination of infected cells by the antibody-mediated effector mechanism, involving antibody-dependent cell cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), and antibody-mediated complement-dependent cytotoxicity (CDC). These mechanisms imply the binding of the Fc area to specific Fcγ receptors (FcγR) present on the membrane of natural killer (NK) cells, macrophages, and neutrophils [ 52 ]. Antibody-enhanced disease (AED) refers to an immunopathological condition provoked by the presence of pre-existing antibodies against a pathogen that does not neutralize the virus [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that after the fourth dose, the proportion of participants with a normal antibody response and those with NAb against the Omicron BA.1 variant was significantly lower in CKD and RD groups compared to the healthy controls. Numerous studies have consistently shown that the presence of neutralizing antibodies is a strong indicator of immune protection against SARS-CoV-2 infection [ 33 ]. Consequently, an impaired neutralizing antibody response suggests limited protection.…”
Section: Discussionmentioning
confidence: 99%